2023
DOI: 10.3389/fphar.2023.1067992
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles mediate biological information delivery: A double-edged sword in cardiac remodeling after myocardial infarction

Abstract: Acute myocardial infarction (AMI) is a severe ischemic disease with high morbidity and mortality worldwide. Maladaptive cardiac remodeling is a series of abnormalities in cardiac structure and function that occurs following myocardial infarction (MI). The pathophysiology of this process can be separated into two distinct phases: the initial inflammatory response, and the subsequent longer-term scar revision that includes the regression of inflammation, neovascularization, and fibrotic scar formation. Extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 233 publications
0
12
0
Order By: Relevance
“…Furthermore, the study demonstrated the ability of MSC-secreted exosomes to mitigate ischemic–reperfusion injury of the myocardium by reducing the infarct size [ 113 , 114 , 115 ]. EVs originating from cardiac stem cells were also discovered to enhance cardiac function in an infarcted heart by reducing fibrosis, initiation angiogenesis, and stimulating the proliferation of cardiomyocytes [ 116 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study demonstrated the ability of MSC-secreted exosomes to mitigate ischemic–reperfusion injury of the myocardium by reducing the infarct size [ 113 , 114 , 115 ]. EVs originating from cardiac stem cells were also discovered to enhance cardiac function in an infarcted heart by reducing fibrosis, initiation angiogenesis, and stimulating the proliferation of cardiomyocytes [ 116 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Ischemic tissue injury is often treated by a skin flap transplantation, which relies heavily on promoting angiogenesis to ensure flap survival. The application of SC-derived exosomes led to a significant enhancement in the survival rate of these transplanted flaps while also increasing the activity of genes that promote the formation of new blood vessels [ 116 , 120 ]. In relation to addressing illnesses linked to malfunctioning vascular barriers, MSC-EVs have displayed potential in lessening pulmonary vascular permeability and lung damage during hemorrhagic shock [ 107 , 121 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Thus, blocking the generation and release of EVs was found to reduce blood pressure in hypertensive rats [ 203 ]. Furthermore, an increase in circulatory EC-EV levels has been found in patients with endothelial dysfunction [ 204 ], obstructive sleep apnea [ 205 ], obesity [ 206 , 207 ], renal failure [ 208 ], coronary artery disease [ 209 ], myocardial infarction [ 210 , 211 , 212 ], β-thalassemia [ 213 ], and stroke [ 214 ]. Nevertheless, it is not clear if the increase in their number contributes to these conditions.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…Different cells or cell-derived vesicles may have a dual function in early inflammation and late scar tissue formation in MI. 197 As a result, while administering cell or cell-inspired preparations, the antifibrotic or profibrotic effects must be considered. Furthermore, the feasibility of the mode of administration requires further investigation.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%